The Influence of Gain-Framed and Loss-Framed Health Messages on Nutrition and Physical Activity Knowledge - Deborah S. Fetter PhD; Madan Dharmar MBBS, PhD; Suzanne Lawry-Hall MS; Jona Pressman BS; Jamie Chapman; Rachel E. Scherr PhD (SAGE Publishing, 2019)
Background . Research remains inconclusive about the most effective frame for encouraging health preventative behaviors. Aims . To examine the impact of gain- and loss-framed health messages on nutrition and physical activity (PA) knowledge in fourth-grade youth participating in the Shaping Healthy Choices Program (SHCP), a multicomponent nutrition program. Methods . Youth were recruited to participate in this 9-month quasi-experimental study and divided into 3 groups: (1) comparison (n = 50), (2) loss-framed (n = 76), and (3) gain-framed (n = 67). All youth participated in the SHCP, and the gain- and loss-framed groups also viewed weekly health messages. Paired t tests or Wilcoxon signed-rank test, ANOVA (analysis of variance), and Bonferroni for multiple comparisons were used for analysis. Results . Youth who participated in the SHCP improved nutrition knowledge (+2.0 points; P < .01) and PA knowledge (+1.8 points; P < .01). Nutrition knowledge improved in the comparison group (+1.3 points; P = .04), loss-framed group (+1.9 points; P = .01), and gain-framed group (+2.6 points; P = .01). Improvements in PA knowledge were also demonstrated in the comparison group (+1.6 points; P < .01), the loss-framed group (+1.3 points; P < .01), and the gain-framed group (+2.5 points; P = .01). There were no significant differences between groups. Youth in the loss-framed group reported a decrease in self-efficacy (−1.2; P = .05), while this was not observed in the other groups. Discussion . The SHCP improves nutrition and PA knowledge, and the positive reinforcement further strengthens some of these improvements, while loss-framed messaging can contribute to undesirable outcomes. Conclusions . Incorporating positive reinforcement through gain-framed messages can be a relatively low-cost avenue for supporting beneficial outcomes.